Treatment of Swine Wastewater Using the Domestic Microalga Halochlorella rubescens KNUA214 for Bioenergy Production and Carotenoid Extraction - Yu-Hee Seo; Jeong-Mi Do; Ho-Seong Suh; Su-Bin Park; Ho-Sung Yoon (Applied Sciences)
The management of swine wastewater (SW) presents significant environmental challenges, requiring solutions that combine effective treatment with resource recovery. This study highlights the dual role of microalgae in wastewater remediation and bioenergy production. H. rubescens KNUA214 was cultivated in media containing varying concentrations of diluted swine wastewater (DSW; 0%, 25%, 50%, and 100%). Cultivating with Blue Green-11 (BG-11) medium + 50% DSW maximized biomass growth, the chlorophyll content, and carotenoid production. Nutrient removal efficiency in 100% DSW over 8 days demonstrated reductions of 59.3% in total nitrogen, 67.7% in ammonia nitrogen, and 40.7% in total phosphorus, confirming the species’ capacity for effective wastewater treatment. The carotenoid analysis using HPLC revealed that astaxanthin, lutein, canthaxanthin, and beta-carotene exhibited the highest levels in BG-11 + 50% DSW. Furthermore, the biomass analyses confirmed its potential for bioenergy applications, with high calorific values and significant polyunsaturated fatty acid concentrations, enhancing its utility for bioenergy and biolubricant production. These findings position H. rubescens KNUA214 as an effective resource for integrating SW management with the sustainable production of high-value biochemicals, offering environmental and economic benefits.